2021
DOI: 10.11622/smedj.2019166
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging of dilated cardiomyopathy: prognostic benefit of identifying late gadolinium enhancement in Asian patients

Abstract: Online first papers have undergone full scientific review and copyediting, but have not been typeset or proofread. To cite this article, use the DOIs number provided. Mandatory typesetting and proofreading will commence with regular print and online publication of the online first papers of the SMJ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Thirty studies with a total of 7541 patients reported major ventricular arrhythmic events, which occurred in 810 patients (10.7%) 4 , 9 , 16 19 , 25 28 , 31 33 , 35 , 37 39 , 42 44 , 46 , 51 , 57 , 60 , 62 , 63 , 66 , 68 , 71 . The pooled OR and rates of major ventricular arrhythmic events were shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thirty studies with a total of 7541 patients reported major ventricular arrhythmic events, which occurred in 810 patients (10.7%) 4 , 9 , 16 19 , 25 28 , 31 33 , 35 , 37 39 , 42 44 , 46 , 51 , 57 , 60 , 62 , 63 , 66 , 68 , 71 . The pooled OR and rates of major ventricular arrhythmic events were shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-four studies with a total of 5807 patients reported cardiovascular mortality, which occurred in 734 patients (12.6%) 9 , 10 , 17 , 21 , 29 31 , 33 , 35 , 37 40 , 43 , 44 , 48 , 51 , 57 , 58 , 62 , 63 , 66 , 68 , 71 . The pooled OR and rates of cardiovascular mortality were shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation